(untitled) (Comparative Professional Pedagogy, 2022)
The article is dedicated to the study of BA, MA and PhD programs in Applied Linguistics at the universities of the USA. Special attention has been paid to Georgetown University where professional training of future specialists in Applied Linguistics has its specific features and experience that can be studied and borrowed into educational systems of developing countries. Special feature of Applied Linguistics study at the university is the ability of students to complete an accelerated Master’s degree program, write a Senior Honor Thesis and participate in inter-disciplinary research in cognitive science, which allows students to combine the study of language with broader study of human mind. The curriculum of Bachelor’s degree program has been analyzed and academic disciplines constituting it have been defined. Requirements to students’ knowledge, abilities and skills have been characterized. It is a notable fact that in American universities and in Georgetown in particular it is a privilege for students to write an Honors Thesis. Only a limited number of students in Applied Linguistics can be bestowed an honor to write it in their senior year of Bachelor’s study. The procedure of writing the Thesis and its presentation have been thoroughly described. Accelerated Master’s degree program that allows students to complete Bachelor’s degree training and start Master’s degree training simultaneously has been analyzed. Traditional Master’s degree program in Language and Communication – a two-year professional program that is based on Applied Sociolinguistics and provides training to students necessary to become professionals capable of using linguistic skills in business, government, non-profitable, technical and educational branches has been presented and its curriculum analyzed. Compulsory and elective academic disciplines have been characterized. It has been defined that after obtaining Master’s degree, students can submit application for PhD degree program in one of the following branches: Applied Linguistics, Computational Linguistics, Sociolinguistics, Theoretical Linguistics, and General Linguistics.